Контроль митної вартості товарів в Україні - Яременко, Дмитро Миколайович; Yaremenko, Dmytro Mykolayovych (Ірпінь, 2024)
Актуальність даної роботи полягає в аналізі теоретико-методологічних основ та практики реалізації контролю митної вартості, визначення проблем та розробка шляхів вдосконалення механізму митного контролю товарів

The relevance of this work lies in the analysis of the theoretical and methodological foundations and practice of the implementation of customs value control, the identification of problems and the development of ways to improve the mechanism of customs control of goods
Control of the customs value of goods in Ukraine
Keywords: експорт; митний контроль; дослідження; імпорт; митне регулювання; митно-тарифна система; export; customs control; research; import; customs regulation; customs tariff system